2011
DOI: 10.1038/nrmicro2508
|View full text |Cite
|
Sign up to set email alerts
|

Are bloodstream leukocytes Trojan Horses for the metastasis of Staphylococcus aureus?

Abstract: Staphylococcus aureus bacteraemia remains very difficult to treat, and a large proportion of cases result in potentially lethal metastatic infection. Unpredictable and persistent bacteraemia in the face of highly active, usually bactericidal antibiotics is the strongest predictor of death or disseminated disease. Although S. aureus has conventionally been considered an extracellular pathogen, much evidence demonstrates that it can survive intracellularly. In this Opinion article, we propose that phagocytes, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
269
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 271 publications
(272 citation statements)
references
References 95 publications
2
269
0
1
Order By: Relevance
“…rsp expression is not required for dissemination of S. aureus from the blood or for deep abscess formation, and we have identified and characterized rsp loss-of-function mutants found in human bacteremia. Thus, our data suggest that S. aureus can adopt an attenuated cytotoxic phenotype, with prolonged intracellular residence (51)(52)(53), which permits effective dissemination of the organism with few initial symptoms, followed by deep abscess establishment. The attenuated toxicity phenotype was not noted in isolates from skin and soft tissue infection (17), suggesting that such attenuated toxicity and intracellular survival may be particularly important in bloodstream infection, as opposed to other forms of infection, such as skin and soft tissue infection.…”
Section: Discussionmentioning
confidence: 99%
“…rsp expression is not required for dissemination of S. aureus from the blood or for deep abscess formation, and we have identified and characterized rsp loss-of-function mutants found in human bacteremia. Thus, our data suggest that S. aureus can adopt an attenuated cytotoxic phenotype, with prolonged intracellular residence (51)(52)(53), which permits effective dissemination of the organism with few initial symptoms, followed by deep abscess establishment. The attenuated toxicity phenotype was not noted in isolates from skin and soft tissue infection (17), suggesting that such attenuated toxicity and intracellular survival may be particularly important in bloodstream infection, as opposed to other forms of infection, such as skin and soft tissue infection.…”
Section: Discussionmentioning
confidence: 99%
“…Following 72 h of infection with F. alocis, the majority of, but not all, neutrophils were apoptotic. Surviving neutrophils could be involved in transport of F. alocis to remote sites, as has been demonstrated for other pathogenic microorganisms, such as Mycobacterium tuberculosis, Burkholderia pseudomallei, and Leishmania major (39)(40)(41)(42). It has been reported that during inflammation, a portion of the neutrophils that have already left the circulation and transmigrated to the tissues can migrate back to the circulation (43).…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular survival within phagocytes may contribute to this disease progression by reducing the effectiveness of phagocyte clearance. In addition, some pathogens actively exploit phagocytes to facilitate traffic between host tissues, and it is possible that a related process may underlie GBS dissemination (37,48).…”
Section: Discussionmentioning
confidence: 99%